MGAT4EP promotes tumor progression and serves as a prognostic marker for breast cancer - Lin Zhong; Jianfeng Zhu; Jie Chen; Xuchu Jin; Liangquan Liu; Shufeng Ji; Jing Luo; Hong Wang (Cancer Biology & Therapy)
Breast cancer remains a global health challenge with varied prognoses despite treatment advancements. Therefore, this study explores the pseudogene MGAT4EP as a potential biomarker and therapeutic target in breast cancer. Using TCGA data and bioinformatics, MGAT4EP was identified as significantly overexpressed in breast cancer tissues and associated with poor prognosis. Multivariate Cox regression confirmed MGAT4EP as important prognostic factor. A clinical prediction model based on MGAT4EP expression showed high accuracy for 1-, 3-, and 5-year survival rates and was translated into a nomogram for clinical application. Functional studies revealed that silencing MGAT4EP via siRNA promoted apoptosis, inhibited migration and invasion in breast cancer cells. RNA-seq, GSEA, and GO analyses linked MGAT4EP to apoptosis and focal adhesion pathways. Notably, knock down of MGAT4EP significantly suppressed tumor growth and metastasis in xenograft and lung metastasis models. Taken together, these findings establish MGAT4EP as an attractive target for metastatic breast cancer and provide a potential a promising therapeutic target for breast cancer treatment.